Sexuality related attitudes and behaviors of turkish university students - (:unkn) unknown (SPRINGER/PLENUM PUBLISHERS, 2007)
In this study, sexual attitudes and behaviors of Turkish university students were explored by taking many influential agents both at the distal and the proximal levels into consideration. A total of 563 students from three universities located in three cities completed a questionnaire that assessed their virginity status, first intercourse, sexual permissiveness, pornography usage, endorsement of traditional sexual double standards, and the perception of parental attitudes about sexuality. The results showed that women and students from rural areas were more traditional and conservative in their attitudes and behaviors regarding sexuality. The perception of maternal restriction about sexuality was related to sexual conservatism, negative affective reaction at first coitus, and endorsing traditional sexual double standards. The results are discussed in terms of various degrees of influences originating from proximal and distal variables in the Turkish context.
Keywords: Sexuality; Virginity; First intercourse; Parental attitudes; Turkey; Sex differences; GENDER-DIFFERENCES; COLLEGE-STUDENTS; SEX; TURKEY; WOMEN; POPULATION; FANTASIES; KNOWLEDGE; CULTURE; URBAN